(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Teachers are of the major factors playing a critical role in the success or failure of any educational system; thus, it is vital to investigate those variables that can impact teachers' performance. The present study attempted to identify the factors contributing to Iranian EFL teachers' online burnout and job satisfaction. The study's population comprised 48 EFL teachers aged 24 to 45, 22 men and 26 women of similar socioeconomic backgrounds. They were the researchers' colleagues, teaching at Iran Language Institute (I. L. I.), where the researcher has been teaching for ten years. They were chosen based on convenience sampling, since they were the most available teachers to be asked to fill the study questionnaires. Two main instruments were used to collect the study data: job burnout and job satisfaction questionnaires. The first is composed of 22 and the latter of 40 items. The questionnaires used Likers scales to estimate the teachers' attitudes. Based on the study achievements collected via analysis of the two questionnaires, it could be concluded that the variables of job satisfaction and job burnout negatively impact each other during the Covid 19 pandemic. In other words, as one variable increases, the other one decreases. Based on the above assumption, it can be claimed that the two variables are closely interrelated, indicating that if the language institutes' chairpeople try to eliminate the factors leading to their teachers' online burnout, they may naturally increase the teachers' satisfaction with their work.